Problem Based Learning to Improve Students’ Grammar Competence at Second Semester Students of English Education Borneo University Tarakan - Fitriawati, Fitriawati; Winarno, Winarno (Linguistics and ELT Journal, 2025)
Grammar proficiency continues to be a significant difficulty for students in higher education, particularly in English as a Foreign Language (EFL) settings.  This burning issue calls for innovative teaching strategies that actively engage learners in language use. The purpose of this study was to analyze the implementation of problem-based learning (PBL) in grammar instruction and evaluate its effectiveness in improving students' grammatical competency. This research employed a collaborative classroom action research design. It was conducted over two cycles to observe the changes in students' grammar performance through iterative interventions. The participants were 32 second-semester students from the English Department. The instruments used to collect data were observation notes and grammar tests designed to measure changes in students' grammar performance. The data were analyzed by comparing the results from two research cycles, focusing on the average scores and the proportion of students achieving the minimum mastery criteria. The results showed a significant improvement: the average student score increased from 62.5 in the first cycle to 72.4 in the second, and the percentage of students who met the minimal mastery criteria rose from 42.3% to 78%. In conclusion, problem-based learning positively impacted students’ grammar proficiency. The implication of this result suggests that PBL not only enhances students' grammatical competence but also improves their speaking and writing abilities by encouraging active communication, fostering motivation, and engaging them in meaningful problem-solving tasks.